EXCHANGING BARBS UNDER THE THEATER BOXES: ROUSSEAU, RAMEAU AND THE QUERELLE DES BOUFFONS (Orfeu, 2020)
The enthusiastic aesthetic debates that were on the agenda in France in the second half of the 18th century and which gave rise to the episode known as Querelle des Bouffons were often reduced to a pamphlet war produced only by the moods of its combatants posted under the theater boxes, and divided into defenders of the French musical tradition and enthusiasts of Italian music, fired mutual criticisms in the form of pamphlets, such as the splinters launched by the self-taught musician and philosopher Jean-Jacques Rousseau against the partisans of French music, especially against his arch-enemy in the Enlightenment music scene, the renowned composer and music theorist JeanPhilippe Rameau. In the present article, far from making a historical reconstruction of the famous Guerre des Bouffons, we seek to analyze the arguments presented by Rousseau in his ardent, but articulate defense of Italian opera as opposed to Versailles opera, such as those set out in his Letter on French music.
Keywords: Musical Aesthetics; Querelle des Bouffons; Jean-Jacques Rousseau; Jean-Philippe Rameau